2022
DOI: 10.3389/fpsyg.2022.899298
|View full text |Cite
|
Sign up to set email alerts
|

The Role of English as a Foreign Language Teachers’ Mindfulness and Compassion in Fostering Students’ Foreign Language Enjoyment

Abstract: With the popularity of positive psychology in English as a Foreign Language (EFL) teaching and learning, learners’ positive emotions have attracted great academic attention. Foreign language enjoyment (FLE) is regarded as a constructive emotion and key component for learners’ academic engagement that is affected by educators’ emotions and psychological attributes. Earlier studies have proved the positive role of educators’ mindfulness and compassion in reducing learners’ negative feelings, boosting their posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Third, the chain-mediating role of academic enjoyment and academic self-concept suggested that in addition to providing academic support, English teachers, as students' psychological coordinators, are suggested to create a positive and active English learning atmosphere for EFL learners. For example, integrating mindfulness and compassion into EFL education (Huang, 2022), offering respect or concern (Gorard & See, 2011), and emphasizing the value of learning English and teaching English with an open, outgoing, and easy-going attitude (Magidson et al, 2014;Pekrun, 2006) are the possible strategies for English teachers to increase students' EFL-related enjoyment and self-concept of ailities in learning English.…”
Section: Researchmentioning
confidence: 99%
“…Third, the chain-mediating role of academic enjoyment and academic self-concept suggested that in addition to providing academic support, English teachers, as students' psychological coordinators, are suggested to create a positive and active English learning atmosphere for EFL learners. For example, integrating mindfulness and compassion into EFL education (Huang, 2022), offering respect or concern (Gorard & See, 2011), and emphasizing the value of learning English and teaching English with an open, outgoing, and easy-going attitude (Magidson et al, 2014;Pekrun, 2006) are the possible strategies for English teachers to increase students' EFL-related enjoyment and self-concept of ailities in learning English.…”
Section: Researchmentioning
confidence: 99%
“…Moreover, adopting an interpersonal mindfulness approach, which entails maintaining open and accepting attitudes toward students, has been shown to facilitate responsive teaching behavior and nurture positive teacher-student relationships [35,36]. Based on the aforementioned research ndings, there are grounds to believe that mindfulness in teaching can enhance teachers' emotional well-being, reduce stress levels, improve classroom management skills, and ultimately enhance teachers' job satisfaction.…”
Section: Mindfulness In Teachingmentioning
confidence: 99%
“…According to Huang (2022), educators' mindfulness and compassion reduce students' negative emotions, boost their positive feelings, and create a harmonious teacher-student relationship. Vetter (2020) supported the benefits of teachers' adoption of mindful qualities as the participating teachers in her research admitted to being more flexible with their students in the classroom which directly created a positive classroom environment for more conducive teaching and learning processes.…”
Section: Literature Reviewmentioning
confidence: 99%